Properties of Roller-Compacted Concrete Pavement Containing Different Waste Material Fillers (Journal of Engineering, 2022)
Waste materials might be utilized in various applications, such as sustainable roller compacted concrete pavements (RCCP), to lessen the negative environmental consequences of construction waste. The impacts of utilizing (brick, thermostone, granite, and ceramic) powders on the mechanical characteristics of RCCP are investigated in this study. To achieve this, the waste materials were crushed, grounded, and blended before being utilized as filler in the RCCP. After the mixes were prepared, compressive strength, splitting tensile strength, flexural strength, water absorption, density, and porosity were all determined. According to the research results, adding some of these powders, mainly brick and granite powder, enhances the mechanical characteristics of RCCP due to their pozzolanic activity and filler effect. Compared to the reference mixture, the usage of ceramic powder provided satisfactory results. When the thermostone powder is utilized in RCCP, unfavorable results occur, resulting in a reduction in the RCCP's mechanical characteristics.